The Role of Historical Insight in Strengthening National Maritime Resilience in the Modern Era - Arafah Pramasto; Baroqah Meyrynaldy; Redi Irawan (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2024)
Indonesia is an archipelago with sea waters covering 77% of its territory. So of course this requires a shared awareness in strengthening maritime resilience, one of which is through understanding history. The method used is a literature study. This research found that one of the oldest historical primary sources in Indonesia, the Kedukan Bukit inscription from Sriwijaya in the 7th century AD, has recorded a river expedition carrying foot soldiers (infantry) as monitors to ensure the safety of the group traveling down the river by boat, from the dangers of enemy ambushes around the river flow, as well as the possibility of serving as technicians in repairing ship damage. Although it still requires further research, this interpretation can also be interpreted as a prototype of successful transportation safety to be applied in minimizing the occurrence of accidents, one of which is the rampant fall of planes into the ocean. Another meaning is to build readiness to prevent bad influences coming from outside, such as disease outbreaks (pandemics), drug smuggling, or the spread of destructive ideologies.